Rhizobacteria and arbuscular mycorrhizal fungi associated with poblano chili in the sierra nevada of Puebla, Mexico - González Mancilla, Apolinar; Almaraz Suarez, Juan José; Ferrera Cerrato, Ronald; Rodríguez Guzmán, María del Pilar; Taboada Gaytán, Oswaldo Rey; Trinidad Santos, Antonio (Revista Mexicana de Ciencias Agrícolas, 2018)
In the lower parts of the Sierra Nevada, Puebla, Mexico, small farmers grow one of the most traditional chilis in Mexican cuisine, poblano chili. The variability in agricultural practices and the characteristics of the soil lead to various microenvironments of production, causing a variation in the populations of beneficial microorganisms. The objective of the present investigation was to quantify the microbial populations [total fungi (HT), total bacteria (BT), phosphate solubilizing bacteria (BSP), nitrogen-fixing bacteria (BFN), auxin-producing bacteria (BPA) and mycorrhizal fungi arbuscular (HMA)] and fruit production in plantations of poblano chili grown in the open field. By means of serial dilutions and seeding in specific media, HT, BT, BSP, BFN and BPA were quantified. The colonization by HMA was determined by the method of thinning and staining with trypan blue. The highest populations of BT and BPA were found in site seven (Huejotzingo), soil with high phosphorus content (428.8 mg kg-1), HT, BSP and BFN were better in site one (San Matias Tlalancaleca), this site did not present the best soil characteristics, but higher altitude, which correlated positively with these microorganisms. Mycorrhizal colonization was better at site nine (Huejotzingo), in a soil with low phosphorus content (44.3 mg kg-1) and moderately alkaline pH (7.6). The yield of fruits was higher in site 8 (Huejotzingo), which presented higher content of organic matter (1.48%) and total nitrogen (0.07%) in soil. Capsicum annuum, nitrogen fixing bacteria, phosphate solubilizing bacteria, auxin producing bacteria.